Multi-owner accredited keyword search over encrypted data - Qi-ying WU; Jian-feng MA; Yin-bin MIAO; Jun-wei ZHANG; Li-min SHEN (Tongxin xuebao)
A sharing multi-owner setting where data was owned by a fixed number of data owners,the existing searchable encryption schemes could not support ciphertext retrieval and fine-grained access control at the same time.For this end,an efficient cryptographic primitive called as multi-owner accredited keyword search over encrypted data scheme was designed,through combining linear secret-sharing technique with searchable encryption schemes,only the data users authorized bymulti-owner by could decrypt the returned results.The formal security analysis shows that the scheme can protect security and privacy under the bilinear Diffie-Hellman assumption.As a further contribution,an empirical study over real-world dataset was conelucted to show the effectiveness and practicability of the scheme.